The Possibility of Applying the Strategy of the Compressed Workweek in Government Agencies in Saudi Arabia: Exploratory Study - Alhajj , Abdulmalek (The Arab Journal of Administration, 2021)
This study aimed to identify the possibility of applying the strategy of the compressed workweek in the governmental agencies of the Kingdom of Saudi Arabia, with the intention of employees’ willingness to work according to this strategy, which form they prefer, the main factors behind their acceptance of the strategy, in addition to identify the main obstacles during the implementation, as well as identify outcomes of this new strategy. The descriptive method and random sample of (1080) employees used in this study. The study found that a majority of respondents strongly desire to work according to this strategy. As well as, the majority of respondents prefer (4) days a week and (9) hours a day. The study also found that a number of social, economic, and personal factors lead to the employee’s acceptance of work according compressed workweek. Regarding to Social factors most employees want to devote more time to family responsibilities, to do balance between work and family life. Regarding to the economic factors: they want to reduce the costs of commuting to the work every day, and reduce the pollution of the environment due to going by car every day, work part-time and manage private projects. Regarding to the personal factors: changing the current traditional framework of the permanence, personal development and continue the study. The study showed that the prominent obstacles might arise during the implementation of this strategy as the following: civil service regulations, differences in the time of the employee and the time of direct supervisor. Finally, respondents strongly agreed that there are several benefits and outcomes for the organization by implementing of this strategy.